Monkeypox (mpox) virus: Classification, origin, transmission, genome organization, antiviral drugs, and molecular diagnosis. Issue 4 (April 2023) - Karagoz, Aysel; Tombuloglu, Huseyin; Alsaeed, Moneerah; Tombuloglu, Guzin; AlRubaish, Abdullah A.; Mahmoud, Amal; Smajlović, Samira; Ćordić, Sabahudin; Rabaan, Ali A.; Alsuhaimi, Ebtesam
Abstract: Monkeypox virus (MPXV) is a double-stranded DNA virus belonging to the Poxviridae family of the genus Orthopoxvirus with two different clades known as West African and Congo Basin. Monkeypox (MPX) is a zoonosis that arises from the MPXV and causes a smallpox-like disease. The endemic disease status of MPX was updated to an outbreak worldwide in 2022. Thus, the condition was declared a global health emergency independent of travel issues, accounting for the primary reason for its prevalence outside Africa. In addition to identified transmission mediators through animal-to-human and human-to-human, especially sexual transmission among men who have sex with men came to prominence in the 2022 global outbreak. Although the severity and prevalence of the disease differ depending on age and gender, some symptoms are commonly observed. Clinical signs such as fever, muscle and headache pain, swollen lymph nodes, and skin rashes in defined body regions are standard and an indicator for the first step of diagnosis. By following the clinical signs, laboratory diagnostic tests like conventional polymerase chain reaction (PCR) or real-time PCR (RT-PCR) are the most common and accurate diagnostic methods. Antiviral drugs such as tecovirimat, cidofovir, and brincidofovir are used for symptomatic treatment. There is no MPXV-specific vaccine; however, currently available vaccines against smallpox enhance the immunization rate. This comprehensive review covers the MPX disease history and the current state of knowledge by assessing broad topics and views related to disease origin, transmission, epidemiology, severity, genome organization and evolution, diagnosis, treatment, and prevention.